Effects of Novel Tacrine Derivatives on Mitochondrial Energy Metabolism and Monoamine Oxidase Activity-In Vitro Study - Hroudová, Jana; Nováková, Tereza; Korábečný, Jan; Maliňák, Dávid; Górecki, Lukáš; Fišar, Zdeněk (Molecular neurobiology, 2021)
The trends of novel AD therapeutics are focused on multitarget-directed ligands (MTDLs), which combine cholinesterase inhibition with additional biological properties such as antioxidant properties to positively affect neuronal energy metabolism as well as mitochondrial function. We examined the in vitro effects of 10 novel MTDLs on the activities of mitochondrial enzymes (electron transport chain complexes and citrate synthase), mitochondrial respiration, and monoamine oxidase isoform (MAO-A and MAO-B) activity. The drug-induced effects of 7-MEOTA-adamantylamine heterodimers (K1011, K1013, K1018, K1020, and K1022) and tacrine/7-MEOTA/6-chlorotacrine-trolox heterodimers (K1046, K1053, K1056, K1060, and K1065) were measured in pig brain mitochondria. Most of the substances inhibited complex I- and complex II-linked respiration at high concentrations; K1046, K1053, K1056, and K1060 resulted in the least inhibition of mitochondrial respiration. Citrate synthase activity was not significantly inhibited by the tested substances; the least inhibition of complex I was observed for compounds K1060 and K1053, while both complex II/III and complex IV activity were markedly inhibited by K1011 and K1018. MAO-A was fully inhibited by K1018 and K1065, and MAO-B was fully inhibited by K1053 and K1065; the other tested drugs were partial inhibitors of both MAO-A and MAO-B. The tacrine/7-MEOTA/6-chlorotacrine-trolox heterodimers K1046, K1053, and K1060 seem to be the most suitable molecules for subsequent in vivo studies. These compounds had balanced inhibitory effects on mitochondrial respiration, with low complex I and complex II/III inhibition and full or partial inhibition of MAO-B activity.
Keywords: Monoamine Oxidase; monoaminoxidasa; Mitochondria; inhibitory MAO; zvířata; Monoamine Oxidase Inhibitors; Alzheimerova nemoc; buněčné dýchání; Electron Transport Complex II; Alzheimer Disease; mitochondrie; energetický metabolismus; Energy Metabolism; respirační komplex II; Swine; prasata; takrin; Cell Respiration; Animals; Tacrine